PERFUSION COMPUTED TOMOGRAPHY IN DETERMINING THE NATURE OF FOCAL PULMONARY LESIONS: CLINICAL AND STATISTIC ANALYSIS - N. I. Sergeev; T. R. Izmailov; P. M. Kotlyarov; I. D. Lagкueva; V. A. Solodky (Сибирский онкологический журнал)
Introduction. Advances in diagnostic imaging techniques have made it possible to measure a large number of blood flow parameters of pathological processes, and one of these techniques is perfusion computed tomography (PCT). The aim of the study was to confirm the reliability of CT perfusion findings in determining the nature of focal pulmonary lesions using statistical analysis data. Material and Methods. A 128-slice CT scanner was used to analyze PCT findings in60 patients with benign and malignant lung tumors. Conclusion. The average PS and TTP values are the main factors in determining the nature of pulmonary lesions. Conclusion: multi-slice CT perfusion imaging is a valuable technique in determining the nature of focal pulmonary lesions. Practical recommendations are given for performing CT-perfusion imaging of the lungs.